2011
DOI: 10.1039/c0dt01453b
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of Rh2(dpf)4(R) where dpf = N,N′-diphenylformamidinate anion and R = CH3, C2H5, C3H7, C4H9 or C5H11

Abstract: The electrosynthesis of Rh(2)(dpf)(4)(R) where dpf is the N,N'-diphenylformamidinate anion and R = CH(3), C(2)H(5), C(3)H(7), C(4)H(9) or C(5)H(11) was carried out in THF containing 0.2 M tetra-n-butylammonium perchlorate (TBAP) and one of several alkyl iodides represented as RI. The initial step in the reaction involved a one-electron reduction of the Rh(2)(4+) unit in Rh(2)(dpf)(4) to its Rh(2)(3+) form followed by a homogeneous reaction involving electrogenerated [Rh(2)(dpf)(4)](-) and the alkyl iodide in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It should be noted that literature and our previous DFT calculations suggested that dehydrate species of dirhodium complexes exhibited more anodic reduction potentials than those of dirhodium complexes with aqua ligands. The dehydrate species [2] and [3] are easily obtained by the simple drying under vacuum at 373 K and can be dissolved in CH 2 Cl 2 , remaining uncoordinated to the Rh 2 center ([1] was insoluble in CH 2 Cl 2 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…It should be noted that literature and our previous DFT calculations suggested that dehydrate species of dirhodium complexes exhibited more anodic reduction potentials than those of dirhodium complexes with aqua ligands. The dehydrate species [2] and [3] are easily obtained by the simple drying under vacuum at 373 K and can be dissolved in CH 2 Cl 2 , remaining uncoordinated to the Rh 2 center ([1] was insoluble in CH 2 Cl 2 ).…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies by Bernhard and Bokarev groups reported that the excited state of [Ir−PS‐1], i. e., *[Ir−PS‐1], could be reductively quenched by TEA, yielding [Ir−PS‐1] − , which can reduces a HEC in the course of photochemical hydrogen evolution reactions. Initially, the UV‐VIS absorption of the AP systems with [2(H 2 O) 2 ] and [3(H 2 O) 2 ] before and after 1 min of visible light irradiation were monitored.…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained with respect to reduction potentials show near- and quasi-reversible Rh 2 4+ to Rh 2 3+ reduction potentials for C3 , C5 , and C6 . The quasi-reversibility is attributed to reaction of the reduced species with the solvent (CH 2 Cl 2 ) to produce a Rh-carbon bond species, similar to that reported by Bear et al Complex C4 exhibits an irreversible reduction at −1.63 V, possibly masked in true nature due the proposed reaction with the CH 2 Cl 2 occurring faster at the 100 mV/s scan rate for this complex. The half-wave potential for compound C6 (−1.18 V) is notably lower than that of compound C3 (−1.34 V).…”
Section: Resultsmentioning
confidence: 99%
“…The rhodium amidinate dimers possess three reversible or quasi-reversible metal-based single-electron redox couples, corresponding to two oxidations and one reduction, as seen in Figure for complex 1 . ,,,,, The redox processes should have a positive trend relative to the Hammett parameter (σ), since a higher positive σ correlates with a stronger electron withdrawing group on the ligand, making the coordinated metal harder to oxidize and easier to reduce. This trend has been observed in the literature for the pendant aryl groups of metal amidinates , and can be seen passing from 8 to 7 to 6 in Figure (top) (see also Table S29 of the Supporting Information for 1 to 4 ).…”
Section: Resultsmentioning
confidence: 99%